Emerging Impact of Non-coding RNAs in the Pathology of Stroke - Ghafouri-Fard, Soudeh; Shirvani-Farsani, Zeinab; Hussen, Bashdar Mahmud; Taheri, Mohammad; Arefian, Noormohammad (Frontiers in Aging Neuroscience, 2021)
Ischemic stroke (IS) is an acute cerebral vascular event with high mortality and morbidity. Though the precise pathophysiologic routes leading to this condition are not entirely clarified, growing evidence from animal and human experiments has exhibited the impact of non-coding RNAs in the pathogenesis of IS. Various lncRNAs namely MALAT1, linc-SLC22A2, linc-OBP2B-1, linc_luo_1172, linc-DHFRL1-4, SNHG15, linc-FAM98A-3, H19, MEG3, ANRIL, MIAT, and GAS5 are possibly involved in the pathogenesis of IS. Meanwhile, lots of miRNAs contribute in this process. Differential expression of lncRNAs and miRNAs in the sera of IS patients versus unaffected individuals has endowed these transcripts the aptitude to distinguish at risk patients. Despite conduction of comprehensive assays for evaluation of the influence of lncRNAs/miRNAs in the pathogenesis of IS, therapeutic impacts of these transcripts in IS have not been clarified. In the present paper, we review the impact of lncRNAs/miRNAs in the pathobiology of IS through assessment of evidence provided by human and animal studies.